Recent Trends in Image Processing and Pattern Recognition. Second International Conference, RTIP2R 2018, Solapur, India, December 21-22, 2018 : Revised Selected Papers /: Second International Conference, RTIP2R 2018, Solapur, India, December 21-22, 2018 : Revised Selected Papers. Part I : ([2019]) - Unknown
No abstract available